Bioorthogonally Cross‐Linked Hyaluronan–Laminin Hydrogels for 3D Neuronal Cell Culture and Biofabrication. Issue 11 (20th February 2022) - Jury, Michael; Matthiesen, Isabelle; Rasti Boroojeni, Fatemeh; Ludwig, Saskia L.; Civitelli, Livia; Winkler, Thomas E.; Selegård, Robert; Herland, Anna; Aili, Daniel
Abstract: Laminins (LNs) are key components in the extracellular matrix of neuronal tissues in the developing brain and neural stem cell niches. LN‐presenting hydrogels can provide a biologically relevant matrix for the 3D culture of neurons toward development of advanced tissue models and cell‐based therapies for the treatment of neurological disorders. Biologically derived hydrogels are rich in fragmented LN and are poorly defined concerning composition, which hampers clinical translation. Engineered hydrogels require elaborate and often cytotoxic chemistries for cross‐linking and LN conjugation and provide limited possibilities to tailor the properties of the materials. Here a modular hydrogel system for neural 3D cell cultures, based on hyaluronan and poly(ethylene glycol), that is cross‐linked and functionalized with human recombinant LN‐521 using bioorthogonal copper‐free click chemistry, is shown. Encapsulated human neuroblastoma cells demonstrate high viability and grow into spheroids. Long‐term neuroepithelial stem cells (lt‐NES) cultured in the hydrogels can undergo spontaneous differentiation to neural fate and demonstrate significantly higher viability than cells cultured without LN. The hydrogels further support the structural integrity of 3D bioprinted structures and maintain high viability of bioprinted and syringe extruded lt‐NES, which can facilitate biofabrication and development of cell‐based therapies. Abstract : This work presents an extracellular matrix mimicking hydrogel for 3D culture of neural cell models. Based on hyaluronic acid and poly(ethylene glycol), the hydrogel immobilizes recombinant laminin‐521, associated with neuronal development. The study demonstrates support of neuroblastoma cell viability, spontaneous human neuroepithelial stem cell differentiation, and the protective effect of the hydrogels during bioprinting and syringe needle ejection.